How hydrology and anthropogenic activity influence the molecular composition and export of dissolved organic matter: Observations along a large river continuum. Issue 5 (11th February 2021) - Zhou, Yongqiang; Yao, Xiaolong; Zhou, Lei; Zhao, Zhonghua; Wang, Xiaolong; Jang, Kyoung‐Soon; Tian, Wei; Zhang, Yunlin; Podgorski, David C.; Spencer, Robert G. M.; Kothawala, Dolly N.; Jeppesen, Erik; et al.
Abstract: Large rivers are the main arteries for transportation of carbon to the ocean; yet, how hydrology and anthropogenic disturbances may change the composition and export of dissolved organic matter along large river continuums is largely unknown. The Yangtze River has a watershed area of 1.80 × 10 6  km 2 . It originates from the Qinghai‐Tibet Plateau and flows 6300 km eastward through the center of China. We collected samples ( n = 271) along the river continuum and analyzed weekly samples at the most downstream situated gauging station in 2017–2018 and gathered long‐term (2006–2018) water quality data. We found higher gross domestic product, population density, and urban and agricultural land use downstream than upstream of the Three Gorges Dam, coinciding with higher dissolved organic carbon (DOC), UV absorption ( a 254 ), specific ultraviolet absorbance (SUVA254 ), parallel factor analysis‐derived C1–C5, aliphatic compounds, and lower a 250 : a 365 and spectral slope ( S 275–295 ). Chemical oxygen demand, humic‐like C1–C2 and C6, and protein‐like C4 and C7 increased, while dissolved oxygen and ammonium decreased with increasing discharge at most of the sites studied, including the intensively monitored downstream site. The annual DOC fluxes were ca. 1.5–1.8 Tg yr −1, and 12–18% was biodegradable in a 28‐d bio‐incubation. Our results highlight that urbanization and stormwater periods enhanced the export of both terrestrial organic‐rich substances and household effluents from nearshore residential areas. Our study emphasizes the continued need to protect the Yangtze River watershed as increased organic carbon loading or altered composition and bio‐lability may change the ecosystem function and carbon cycling.